6*(b-3)=10-2*(b+2) и 83+5*(у-3)=3*(8у-9)

baget97ozu06u baget97ozu06u    2   02.06.2019 08:40    2

Ответы
Lina300333 Lina300333  03.07.2020 06:47
6*(b-3)=10-2*(b+2)
6b-18=10-2b-4
6b+2b=18+10-4
8b=24
b=24/8
b=3
83+5*(у-3)=3*(8у-9)
83+5y-15=24y-27
5y-24y=-83+15-27
-19y=-95
y=-95/-19
y=5
ПОКАЗАТЬ ОТВЕТЫ
Danila1367 Danila1367  03.07.2020 06:47
6 * (b - 3) = 10 - 2 * (b + 2)
6b - 18 = 10 - 2b - 4
6b + 2b = 10 + 18 - 4
8b = 28 - 4
8b = 24
b = 24 : 8
b = 3
ответ: b = 3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика